2022
DOI: 10.21608/puj.2022.156355.1185
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells therapy research for the treatment of parasitic infections

Abstract: Parasitic diseases have significant global economic, environmental, and public health impacts. In recent years, stem cells therapy has become a very promising and advanced scientific research topic. Since stem cells are the primary, unspecialized mother of all cells, they have the ability to differentiate into specialized cells. Besides, they have a remarkable potential to develop into many different cell types in the body to replace the damaged tissues. Recently, researchers experimentally investigated the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Studies have shown that MSC therapy reduces the size and severity of hydatid cysts, and provides an alternative to traditional surgical methods 11,12 . Using MSC therapy for hydatid cyst disease is an inspiring development in regenerative medicine, which help the treatment 13 . The current study aimed to explore the properties and therapeutic potential of MSCs, their role in the treatment of hydatid cyst disease, and the advantages of using MSC therapy, compared to traditional treatment methods.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that MSC therapy reduces the size and severity of hydatid cysts, and provides an alternative to traditional surgical methods 11,12 . Using MSC therapy for hydatid cyst disease is an inspiring development in regenerative medicine, which help the treatment 13 . The current study aimed to explore the properties and therapeutic potential of MSCs, their role in the treatment of hydatid cyst disease, and the advantages of using MSC therapy, compared to traditional treatment methods.…”
Section: Introductionmentioning
confidence: 99%